The Transactional Leadership and Employee Job Satisfaction: Exploring the Mediating Effect of Job Environment Inside SMEs Human Resource Improvement - Inriani, Inriani; Baso Rachim, Andi Farid; Abdullah, Salma; Mustafa, Muh. Yushar (Entrepreneurship, Management, and Business Research Journal, 2025)
Despite numerous studies having been conducted in explaining the role of transactional leadership on employee job satisfaction, this study finds that there is a lack of research in examining the mediation effect of job environment on the relationship of transactional leadership and job satisfaction, specifically in the context of SMEs in emerging countries. Therefore, this study aims to investigate the relationship between transactional leadership and employee job satisfaction within SMEs, with the special emphasis on the mediating effect of job environment. By examining the phenomenon above through a quantitative methodology approach and the application of partial least square measurement, this study finds that in a sample size of 101 SMEs, transactional leadership positively and significantly affects both job environment and employee job satisfaction. Likewise, the role of job environment does affect employee job satisfaction positively and significantly. Intriguingly, this study also finds that job environment has a positive and significant mediating effect on the relationship between transactional leadership and employee job satisfaction. Moreover, the outcome of this study is correspondingly expected to contribute theoretically and managerially to the body of knowledge by offering an insight that later helps managers of SMEs to enhance their employee satisfaction.